2020
DOI: 10.3390/nu12041069
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Polyunsaturated Fatty Acids as Protectors against Calcium Oxalate Renal Stone Formation: A Review

Abstract: In the pathogenesis of hypercalciuria and hyperoxaluria, n-6 polyunsaturated fatty acids (PUFAs) have been implicated by virtue of their metabolic links with arachidonic acid (AA) and prostaglandin PGE2. Studies have also shown that n-3 PUFAs, particularly those in fish oil—eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)—can serve as competitive substrates for AA in the n-6 series and can be incorporated into cell membrane phospholipids in the latter’s place, thereby reducing urinary excretions of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…PREG, pregnenolone; THDOC, tetrahydrodeoxycorticosterone; THF, tetrahydrocortisol; tRA, all-transretinoic acid promoted kidney stone formation. 42 Based on our results and other studies on PGE2, we assume that there is a positive feedback mechanism between PGE2 and kidney stone formation, which may promote the development and recurrence of kidney stones.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…PREG, pregnenolone; THDOC, tetrahydrodeoxycorticosterone; THF, tetrahydrocortisol; tRA, all-transretinoic acid promoted kidney stone formation. 42 Based on our results and other studies on PGE2, we assume that there is a positive feedback mechanism between PGE2 and kidney stone formation, which may promote the development and recurrence of kidney stones.…”
Section: Discussionsupporting
confidence: 69%
“…Specifically, more PGE2 was secreted by the renal epithelial cells in the presence of CaOx monohydrate crystals 41 . What is worse, the elevated PGE2 further increased calcium excretion by affecting renal tubular function and intestinal calcium absorption, and mediated apoptosis of renal tubular epithelial cells by inducing oxidative stress, all of which promoted kidney stone formation 42 . Based on our results and other studies on PGE2, we assume that there is a positive feedback mechanism between PGE2 and kidney stone formation, which may promote the development and recurrence of kidney stones.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated the role of fish oil administration in the dietary management of stone formation. Fish oil supplementation was found to reduce oxalate excretion in healthy subjects [130], and to decrease urinary excretion of calcium and/or oxalate in calcium stone patients in most trials [119]. Further studies should identify those patients who benefit most from n-3 polyunsaturated fatty acid supplementation.…”
Section: Fatmentioning
confidence: 98%
“…Studies have suggested that the dietary fatty acid pattern, especially the ratio of n-6 to n-3 polyunsaturated fatty acids, may affect the risk of calcium oxalate stone formation through various complex mechanisms [119]. An abnormal concentration of arachidonic acid (C20:4n-6) in plasma and erythrocyte membrane phospholipids was found in idiopathic calcium oxalate stone patients compared to healthy controls [120].…”
Section: Fatmentioning
confidence: 99%
“…Notably, although the studies reviewed by Rodgers and Siener [25] were inhomogeneous with regard to study design; type, dosage, frequency of administration and duration of use of PUFAs; and metabolic background and stone composition of study subjects, the authors concluded that daily fish oil supplementation, consisting of 1.3 g eicosapentaenoic acid (EPA) and 1.0 g docosahexaenoic acid (DHA) is advantageous in stone formers with hypercalciuria and/or hyperoxaluria [25].…”
Section: Fish Oilmentioning
confidence: 99%